Anthocyanins from Malus spp. inhibit the activity of Gymnosporangium yamadae by downregulating the expression of WSC, RLM1, and PMA1 - Wang, Yu; An, Hong; Guo, Yan-Nan; Wang, Qian; Shang, Yuan-Yuan; Chen, Ming-Kun; Liu, Yi-Xin; Meng, Jia-Xin; Zhang, Shuang-Yu; Wei, Jun; Li, Hou-Hua (Frontiers in Microbiology, 2023)
Malus plants are frequently devastated by the apple rust caused by Gymnosporangium yamadae Miyabe. When rust occurs, most Malus spp. and cultivars produce yellow spots, which are more severe, whereas a few cultivars accumulate anthocyanins around rust spots, forming red spots that inhibit the expansion of the affected area and might confer rust resistance. Inoculation experiments showed that Malus spp. with red spots had a significantly lower rust severity. Compared with M. micromalus, M. ‘Profusion’, with red spots, accumulated more anthocyanins. Anthocyanins exhibited concentration-dependent antifungal activity against G. yamadae by inhibiting teliospores germination. Morphological observations and the leakage of teliospores intracellular contents evidenced that anthocyanins destroyed cell integrity. Transcriptome data of anthocyanins-treated teliospores showed that differentially expressed genes were enriched in cell wall and membrane metabolism-related pathways. Obvious cell atrophy in peridial cells and aeciospores was observed at the rust spots of M. ‘Profusion’. Moreover, WSC, RLM1, and PMA1 in the cell wall and membrane metabolic pathways were progressively downregulated with increasing anthocyanins content, both in the in vitro treatment and in Malus spp. Our results suggest that anthocyanins play an anti-rust role by downregulating the expression of WSC, RLM1, and PMA1 to destroy the cell integrity of G. yamadae.